1997
DOI: 10.3950/jibiinkoka.100.326
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Pollen Counts of Japanese Cedar to Weather Factors in Isehara City, Kanagawa.

Abstract: We investigated the relationship of pollen counts of Japanese cedar to 9 different weather factors including means of the highest, and lowest temperatures, variation in temperatures mean of the lowest humidity on a day, daily mean, maximum wind velocity and daily wind direction in 1991, 1992, 1993 and 1995 Prefecture. The results were as follows : 1.In each year, the highest temperature and the mean humidity were statistically related to the maximum pollen counts of Japanese cedar in the air. 2.Mean pollen cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…4b shows that peaks of airborne pollen grains appeared on March 21 under higher wind speed and temperature than the previous day. Tamura et al (1997) concluded that the highest temperature was statistically related to the maximum pollen counts of Japanese cedar in the air. The wind speed shown in Fig.…”
Section: Behavior Of Pollen Grains During Thementioning
confidence: 99%
“…4b shows that peaks of airborne pollen grains appeared on March 21 under higher wind speed and temperature than the previous day. Tamura et al (1997) concluded that the highest temperature was statistically related to the maximum pollen counts of Japanese cedar in the air. The wind speed shown in Fig.…”
Section: Behavior Of Pollen Grains During Thementioning
confidence: 99%
“…It has been shown that pollen counts rise with increasing temperatures (Tamura et al, Ahlholm et al). 20,21 In addition, increased atmospheric carbon dioxide provides enhanced 'fertilization' of pollens such as ragweed (Ziska and Caulfield, 2000). 22 Elsewhere, the increased flooding that may be one outcome of climate change may promote further growth of mold and fungal growth in affected areas, leading in turn to increases in associated respiratory ill-health.…”
Section: Air Pollutionmentioning
confidence: 99%